Biceps Femoris Injury a Rarity: A Case Report - Strasser, Roland; Wein, Thomas; Wieder, Marc; Erhardt, Johannes; Kaufmann, Jörg (The Surgery Journal, 2017)
Isolated biceps femoris rupture is a rare injury associated with limitation in the function of the knee. We present a 65-year-old man who sustained an isolated complete rupture of the tendon of the biceps femoris. The diagnostic was reached after clinical examination and magnetic resonance imaging of the affected knee. This case was treated with a surgical tendon reconstruction. The outcome was good and the patient was able to walk normally again without limitation, even if he did not comply with our recommendation.
Keywords: biceps femoris knee joint; rupture; suture